WHY WE HAVE TO REFORM MIDWIFERY EDUCATION? - Esti Nugraheny; Yanti Yanti; Hermanto Tri Joewono (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2022)
Background: Learner, methods and contents are three important parts of the learning variables beside lecturer, academic environment and patients. Facts and new findings show that we need to reform these learning variables accordingly especially in Obstetrics and Midwifery domainGaps:maternal deaths is still high despite higher number of obstetricians, doctors and midwives; as well asthe government has encouraged an increase in the number of institutions providing midwifery study programs. On the other hand, new paradigm in education has been ordered by the Ministry of Education such as student-centred learning, Outcome-based education, and also other approaches suggested by expert in medical education such as holistic education, bedside teaching, feedback & reflection, and problem based learning. Thus modify educational content and method in obstetrics and midwivery inline with new facts and findings and appropriate methods is necessary.Recommendation: One alternative to modify educational content and methods in midwifery education that can be implemented in clinical learning is the continuity of care approach accompanied by continuous feedback. This approach is proven to be able to reduce maternal mortality and as an effort to synergize education in an effort to achieve government program targets. However, in reality, midwifery education institutions have not fully adopted this approach. So there is a need for leadership commitment to carry out learning reforms with a sustainable curriculum approach, continuous feedback, continuous assessment, continuous midwifery care and continuous supervision so that learning outcomes as outputs and reducing maternal mortality as an outcome can be as expected.